2023
DOI: 10.1001/jamanetworkopen.2023.12684
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the Complex Web of Out-of-Hospital Cardiac Arrest Socioeconomic Disparities

Abstract: Out-of-hospital cardiac arrest (OHCA) is a time sensitive and highly mortal condition with substantial variation in survival rates globally. 1 Optimizing OHCA outcomes requires complex coordination of multiple care systems and treatment modalities. Many aspects in the cascade of cardiac arrest care, from prevention to hospital-based postarrest care, are attributed to these variations in outcomes.Patient race, ethnicity, and socioeconomic position (SEP) 2 are also all associated with unacceptable disparities in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Neighborhood racial composition and socioeconomic status have been shown to be associated with differences in rates of bystander CPR, leading to disparities in survival to discharge and survival with good neurological status. 3,[10][11][12] In our prior OHCA research, we found that measures of racial and economic segregation are predictors of disparities in outcomes; Medicare beneficiaries residing in more highly segregated Black population and lower income ZIP codes had decreased likelihood of survival to discharge and survival at one year, as well as increased risk of readmission at 30 days. 13,14 However, prehospital predictors are not available in claims data, such as initial rhythm or the presence of a bystander CPR (B-CPR).…”
Section: Introductionmentioning
confidence: 89%
“…Neighborhood racial composition and socioeconomic status have been shown to be associated with differences in rates of bystander CPR, leading to disparities in survival to discharge and survival with good neurological status. 3,[10][11][12] In our prior OHCA research, we found that measures of racial and economic segregation are predictors of disparities in outcomes; Medicare beneficiaries residing in more highly segregated Black population and lower income ZIP codes had decreased likelihood of survival to discharge and survival at one year, as well as increased risk of readmission at 30 days. 13,14 However, prehospital predictors are not available in claims data, such as initial rhythm or the presence of a bystander CPR (B-CPR).…”
Section: Introductionmentioning
confidence: 89%